Small and medium-sized (SME) companies are not investing in digital tools and IT – why? : A research into SME digital tools and IT adoption factors - Matintupa, Johannes (fi=Turun yliopisto|en=University of Turku|, 2018)
Prior research and media coverage over recent years have stated that small – and medium-sized companies (SMEs) are lagging behind in digitalisation and the adoption of digital tools and IT. This master thesis research studies SME IT adoption factors with research question; What are the IT and digital tools adoption affecting factors in SME environment? The master thesis examines different models, solutions and outsourced IT consultancy available for SME companies to use in gaining understanding on their business. Research builds on existing background literature on the topic and based on prior literature found factors, two empirical studies are conducted; a theme based focus interview of IT service providers, and, a data analysis of available data on SME companies research. The research discovers whether same IT adoption factors found from literature are found from SME companies functioning in Turku and recommendations are given to IT specialists working in the field. Results show SME IT adoption taking place under various affecting factors and the environment SMEs function in is changing rapidly. Key findings describe SME business without long term strategies and characterised by limited resources of time, financials and expertise which cause uncertainties and negative attitudes towards IT investments. The available IT solutions are many times perceived as not beneficial, too complex to use or taking too much resources. Relations between SME companies and outsourced IT companies require trust and transparency in order to work. Conclusions state that SMEs need to put efforts in understanding their business processes in order to improving their business. This understanding enables correct IT solution selection. SMEs need to invest in internal capabilities and external relationships. IT service providers have a key role in supporting SME digitalisation. They need to act transparently and foster trust, and the changing ways of doing business puts requirements on IT companies to renew their structures as well. IT companies have a key role in enabling well-argued SME IT decision-making which makes sense to the SME company owners or decision-makers.